2021
DOI: 10.1016/j.jss.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation with Right Ventricular Assist Device for COVID-19 ARDS

Abstract: Background: Right ventricular failure is an underrecognized consequence of COVID-19 pneumonia. Those with severe disease are treated with extracorporeal membrane oxygenation (ECMO) but with poor outcomes. Concomitant right ventricular assist device (RVAD) may be beneficial. Methods: A retrospective analysis of intensive care unit patients admitted with COVID-19 ARDS (Acute Respiratory Distress Syndrome) was performed. Non-intubated patients, those with acute kidney injury, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 32 publications
(55 reference statements)
3
69
1
Order By: Relevance
“…1 , Additional file 1 : Table S4) [ 3 , 5 , 16 65 ]. All studies were retrospective and observational in nature; 22 studies were conducted by studies centres from Europe [ 5 , 17 , 19 , 23 , 27 , 29 , 31 – 34 , 36 , 39 , 42 , 43 , 45 , 46 , 50 , 55 , 56 , 60 , 63 , 65 ], 17 from North America [ 16 , 18 , 20 22 , 24 , 25 , 37 , 40 , 47 , 48 , 52 54 , 57 , 58 , 61 ], 6 from the Asia–Pacific [ 26 , 28 , 35 , 38 , 41 , 44 ], 2 from South-West Asia and Africa,[ 51 , 62 ] 2 from Latin America [ 30 , 64 ], and 3 were studies conducted by centres from multiple ELSO regions [ 3 , 49 , 59 ], of which 2 were based on registry data [ 3 , 49 ]. The pooled age was 52.5 years (95% CI 50.7 to 54.3), and the majority of patients were male (75.0%, 95% CI 72.4% to 77.4%) and obese (BMI: 31.0, 95% CI 30.2 to 31.8).…”
Section: Resultsmentioning
confidence: 99%
“…1 , Additional file 1 : Table S4) [ 3 , 5 , 16 65 ]. All studies were retrospective and observational in nature; 22 studies were conducted by studies centres from Europe [ 5 , 17 , 19 , 23 , 27 , 29 , 31 – 34 , 36 , 39 , 42 , 43 , 45 , 46 , 50 , 55 , 56 , 60 , 63 , 65 ], 17 from North America [ 16 , 18 , 20 22 , 24 , 25 , 37 , 40 , 47 , 48 , 52 54 , 57 , 58 , 61 ], 6 from the Asia–Pacific [ 26 , 28 , 35 , 38 , 41 , 44 ], 2 from South-West Asia and Africa,[ 51 , 62 ] 2 from Latin America [ 30 , 64 ], and 3 were studies conducted by centres from multiple ELSO regions [ 3 , 49 , 59 ], of which 2 were based on registry data [ 3 , 49 ]. The pooled age was 52.5 years (95% CI 50.7 to 54.3), and the majority of patients were male (75.0%, 95% CI 72.4% to 77.4%) and obese (BMI: 31.0, 95% CI 30.2 to 31.8).…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of the ProtekDuo TM cannula, in comparison to its competitors, is the insertion within the right IJ vein, permitting full ambulation within recipients. RVAD-ECMO with the ProtekDuo TM in patients with COVID-19 in comparison to mechanical ventilation alone has been to show to reveal no increase in secondary end-organ damage, with higher in-hospital and 30-day survival in the RVAD-ECMO cohort, leading to a conclusion to prioritize RV support in these patients 11 . RVAD-ECMO configuration with the ProtekDuo TM single dual-lumen cannula, in comparison to conventional Crescent TM VV-ECMO circuit in severely ill COVID-19 patients has not yet been studied, though our case showcases there appears to be a benefit through addition of right ventricular support.…”
Section: Discussionmentioning
confidence: 99%
“…33 Veno-pulmonary arterial ECMO led to a threefold survival benefit compared with maximum ventilation support alone and that was observed across all age and body mass index groups. 33 In a small retrospective analysis, Cain et al 35 found that early use of percutaneous RVAD (at the time of ECMO initiation) may improve mortality in patients with severe COVID-19 lung injury. It is possible that early mechanical RV unloading/support in the context of severe acute respiratory failure combined with extracorporeal oxygenation, which allows application of lung- and RV-protective ventilation, accounts for the observed outcome.…”
Section: Veno-pulmonary Arterial Extracorporeal Membrane Oxygenation ...mentioning
confidence: 99%